Analysis of Work Readiness Research Instruments for Vocational High School of the Mechanical Engineering Program - Nur Aini Susanti; Suparji Suparji; Tri Wrahatnolo; Syaad Patmanthara; Ekohariadi Ekohariadi; Harmanto Harmanto; Achmad Imam Agung; Arie Wardhono; Hanna Zakiyya; Yuli Sutoto Nugroho (IJORER : International Journal of Recent Educational Research, 2024)
Objective: One of the levels of education in Indonesia is Vocational High School (VHS). VHS provides various skills programs, and VHS’s graduates should have greater opportunities to work based on their competencies. However, in East Java, most of the unemployed are VHS graduates. One of the skills programs at VHS is the Mechanical Engineering Skills program. The research purpose was to analyze the instrument research of work readiness vocational high school of the Mechanical Engineering program. Method: This research used a quantitative method. Instrument Work Readiness (WR) with variable problem-solving skills (PSS), Technology Skills (TS), Teamwork Skills (TWS) and Self-management Skills (SMS). Validity test of instrument used software Winstep Rasch analysis and reliability test of instrument used software Stata. The instrument, which has been validated by experts, was tested on 30 respondents. Results: aspect validity about test quality, model of legibility, and instrument sheet. Instrument validity of PSS was advisability 91.3%, CVR 0.92 and reliability 0.797, TS was advisability 93.6%, CVR 0.95 and reliability 0.491, TWS was advisability 90.3%, CVR 0.87 and reliability 0.798, SMS was advisability 92.6%, CVR 0.86 and reliability 0.941, WR advisability 95%, CVR 0.95 and reliability 0.946. Novelty: New model research instrument for measuring problem-solving skills, technology skills, teamwork skills, and self-management skills on the work readiness of students at Machining Engineering Vocational High School in East Java together. Machining engineering specially measured Computer Numerically Controlled (CNC) competence likely design workpiece, CNC programming, programming simulation, and inputting CNC programming.